(untitled) (Revista de História da UEG (REVHIST), 2024)
The aim of this article is to analyze the use of fama in the exercise of power by the rulers of the Kingdom of Sicily-Naples. Through the study of two trials suffered by Count Adenolf IV of Acerra, one in 1286 for treason and the other in 1293 for a heinous crime, I seek to answer the question: Is fama a useful category for analyzing the exercise of power by the Angevin kings? I show that fama becomes an essential element in the trial when an inquisitorial model is developed, in which the defendant’s reputation is used to aid the decision. Thus, I show that the first trial and the fama that Adenolf IV acquired after it was important in ensuring his conviction in the second. Furthermore, for political reasons, the documentation relating to the 1293 trial refers to the count based on the accusation of the first trial, leaving aside the heinous crime. This was due to the differences in the exercise of justice and the authority of the monarch in the two areas where the trials took place: while in the Kingdom of Sicily-Naples the ruler was directly answerable to the pope, in the County of Provence his authority was more independent. For the analysis, I use John Pocock’s work on political language, especially the idea of the speech act, a tactical and linguistic maneuver that seeks to convince. Keywords: Exercise of power. Fama. Treason. Heinous crime. Angevins of Naples.